Kompetensi Komunikasi Organisasi dan Model 4C Guna Branding dan Membangun Reputasi Melalui Media Sosial - Rosmawaty Hilderiah Pandjaitan; Leila Mona Ganiem; Yoyoh Hereyah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The Association of Indonesian Catering Experts (Ikaboga Indonesia) is a social organization with 28 DPDs in 28 Provinces, providing many courses and training in Catering. It is not easy to control; it requires organizational communication competence because it is essential to lead and maintain the organization's running and effectively achieve organizational goals. In the 4C Model, competencies (critical thinking, communication, collaboration, and creativity) are 21st Century Skills. So that Ikaboga Indonesia's activities are widely known and trusted, this can include using social media as a branding and reputation-building medium. Moreover, it is known that 60% of Indonesia's population uses social media. Branding is essential because it can place an organization's name above other competitors, and reputation is critical because it can carry positive attributes and provide sustainable profits. This is the urgency and background of this training. The aim is for Ikaboga Indonesia Chairs to improve their organizational communication competence and the 4C Model, both for branding and building reputation through social media. This activity was carried out hybrid (offline and online) on February 6, 2024, in the Hall, Fl. 7 Tedja Buana Building, Menteng, Central Jakarta. It uses presentation, question and answer, discussion, practice, and simulation methods. One hundred fifty-nine participants participated, 44 (27.8%) offline and 115 (72.2%) online. Get positive responses, rated as needed, helpful, and engaging.